Effect of the Epley Maneuver and Brandt-Daroff Exercise on Benign Paroxysmal Positional Vertigo Involving the Posterior Semicircular Canal Cupulolithiasis: A Randomized Clinical Trial - Choi, Seo-Young; Cho, Jae Wook; Choi, Jae-Hwan; Oh, Eun Hye; Choi, Kwang-Dong (Frontiers in Neurology, 2020)
Abstract Objective To investigate the therapeutic efficacies of the Epley maneuver and Brandt-Daroff (BD) exercise in patients with benign paroxysmal positional vertigo involving the posterior semicircular canal cupulolithiasis (PC-BPPV-cu). Methods We conducted a randomized clinical trial to evaluate the therapeutic effect of the Epley maneuver and BD exercise in patients with PC-BPPV-cu. Patients were randomly assigned to undergo the Epley maneuver (n=29) or BD exercise (n=33). The primary outcome was an immediate resolution of positional nystagmus within 1 hour after a single treatment of each maneuver on the visit day. Secondary outcomes included the resolution of positional nystagmus at 1 week, the change of maximal slow phase velocity (mSPV) of positional nystagmus, and dizziness handicap inventory (DHI) immediately and at 1 week. Results Immediate resolution occurred in none of 29 patients in the Epley maneuver group and only 1 of 33 patients in the BD exercise group. The Epley maneuver and BD exercise had an equivalent effect at 1 week in treating PC-BPPV-cu in terms of resolving positional nystagmus (48 vs. 36%, p=0.436) and the decrease of mSPV and DHI. Conclusion Neither the Epley maneuver nor BD exercise has an immediate therapeutic effect in treating PC-BPPV-cu. Clear classification of PC-BPPV should be required at the time of different pathology and different treatment response.